2006
DOI: 10.1097/01.brs.0000224167.18483.14
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Follow-up of Lumbar Spine Endplate (Modic) Changes

Abstract: Modic changes are common MRI findings in patients with degenerative lumbar disc disease. We found evidence that Modic Type II changes may be less stable than previously assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
163
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 15 publications
16
163
1
4
Order By: Relevance
“…An inflammatory process in endplates with M1 subchondral signal changes has been suggested to be induced by tumor necrosis factor (TNF) [18]. In a 3-year follow-up of sciatica patients [12], new subchondral signal abnormalities were seldom found to be associated with endplate lesions, in contrast to our study, but the follow-up was shorter and the prevalence of subchondral hypointensities was lower and none was uniformly hypointense at baseline.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…An inflammatory process in endplates with M1 subchondral signal changes has been suggested to be induced by tumor necrosis factor (TNF) [18]. In a 3-year follow-up of sciatica patients [12], new subchondral signal abnormalities were seldom found to be associated with endplate lesions, in contrast to our study, but the follow-up was shorter and the prevalence of subchondral hypointensities was lower and none was uniformly hypointense at baseline.…”
Section: Discussioncontrasting
confidence: 93%
“…The finding of three new hypointensities appearing within previous hyperintensities may be explained by new subchondral edema in a region with earlier fatty degeneration. Reverse transformation of M2 to M1 has been reported earlier [12,14]. Thirty-four percent of M1s persisted or enlarged, suggesting that the phase of subchondral edema may last even for years.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Modic-associated proinflammatory biochemical mediators have been suggested to be a major origin of pain [6]. MT1 converts to either MT2 or to a normal stage from 14 months to 3 years [20]. However, one possible explanation is that the acute inflammation may have resolved, even though MT1 was still present on the MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have shown that Modic changes show a high prevalence in patients with degenerative disc disease and are seen in 23% of non-operatively treated sciatica patients [30], with a high rate of increased changes following microdiscectomy [6]. Some authors associate Modic Type 1 changes with low back pain, although conversions to ''more benign'' Type 2 changes seem possible [31,32].…”
Section: Discussionmentioning
confidence: 99%